(untitled) (INTERNATIONAL JOURNAL OF CONSTRUCTION ENGINEERING (IJCE), 2020)
The essence of ground improvement is to enhance the engineering properties of weak soils to provide stability and sufficient bearing capacity for construction and other engineering purposes. Deep soil mixing is one method that has been widely employed for this purpose due to the environmental nature and efficiency of this method. In deep soil mixing, the amount of binder to be mixed with the weak soil depends on the initial moisture content of the surrounding soil. Several researchers have reported on this method of soil improvement through laboratory experiments, in situ testing and numerical modelling. Most literatures reviewed in this study have shown that previous studies by different researchers on weak soil improvement using deep mixing techniques have focused on the mechanical properties such as compressive strength, stiffness, modulus of elasticity and consolidation behaviour of the improved ground. For example, Ali et al., (2012), Lin and Wong, 1999, Fang et al., (2001), Porbaha et al., (2001), Yin, (2001), Porbaha, (2002), Farouk and Shahien (2013), Tao, Jim and Jing, 2014) etc. Others focused on the effect of soil type, binder type, binder content, water-cement ratio and area replacement ratio on the mechanical properties of the improved ground, for example; Nur et al. (2013), Terashi et al., (1977), Kitazume and Terashi, (2012), Farouk and Shahien, (2013) etc. This paper therefore serves as a quick guide on understanding the performance of DMC improved ground based on what has been reported in literatures.